Analysis of Al-Qur'an Tafsir: Tafsir Study with Riwayah and Dirayah Approach - Unung Lisnawati; Hafid; Cecep Anwar; Abu Hanifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article aims to analyze and compare two primary methods in the study of tafsir: Tafsir Riwayah/Bi Al Ma'tsur and Tafsir Dirayah/Bi Al Ra'y, and to explore how their integration can enrich understanding of the Qur'an. The research method used is a case study, which involves collecting and analyzing literature related to tafsir from various sources, including relevant books, articles, and scholarly works. The research results show that Tafsir Riwayah/Bi Al Ma'tsur, which is based on history and authoritative sources, provides a historical and traditional context in interpreting the verses of the Qur'an. On the other hand, Tafsir Dirayah/Bi Al Ra'y offers a more dynamic and contextual approach, providing space for critical reasoning in understanding the meaning of the text. The integration of these two approaches enables the creation of a more holistic and in-depth understanding of the Al-Qur'an, so that it is able to answer the challenges of the times that continue to develop.